2015
DOI: 10.1016/s2352-3018(15)00108-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of immediate antiretroviral therapy versus CD4-based initiation in HIV-positive individuals in high-income countries: observational cohort study

Abstract: Summary Background Recommendations have differed nationally and internationally with respect to the best time to start antiretroviral therapy (cART). We compared effectiveness of three strategies for initiation of cART in high-income countries for HIV-positive individuals who do not have AIDS: immediate universal cART initiation, cART initiation at a CD4 cell count below 500, and cART initiation at a CD4 cell count below 350 cells/mm3. Methods We used data from the HIV-CAUSAL collaboration of cohorts in Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 33 publications
(34 reference statements)
5
66
0
Order By: Relevance
“…The reduction in absolute risk was smaller for non-AIDS mortality. While small, the estimated benefits of immediate initiation on the all-cause mortality of these older populations are larger than those estimated among all individuals in the HIV-CAUSAL Collaboration (median age 37 years) 22: the 7-year risk of all-cause mortality for immediate initiation was only 0.25% (95% CI 0.40,0.37) lower than the risk under initiation at CD4 count<350 cells/mm 3 . These findings suggest that in older HIV-positive patients the benefits of immediate ART initiation on mortality are not offset by age-related comorbidities and potential effects of polypharmacy.…”
Section: Discussionmentioning
confidence: 81%
“…The reduction in absolute risk was smaller for non-AIDS mortality. While small, the estimated benefits of immediate initiation on the all-cause mortality of these older populations are larger than those estimated among all individuals in the HIV-CAUSAL Collaboration (median age 37 years) 22: the 7-year risk of all-cause mortality for immediate initiation was only 0.25% (95% CI 0.40,0.37) lower than the risk under initiation at CD4 count<350 cells/mm 3 . These findings suggest that in older HIV-positive patients the benefits of immediate ART initiation on mortality are not offset by age-related comorbidities and potential effects of polypharmacy.…”
Section: Discussionmentioning
confidence: 81%
“…only1[57]2[69,78]3Regional lang. & English17[40,41,43,44,4749,53,54,56,5962,7375]7[40,41,70,76,77,79,80]22 b  Not stated11[42,45,5052,55,58,6366]5[46,67,68,71,72]16AI – anal intercourse, VI – vaginal intercourse, UAI – unprotected anal intercourse, UVI – unprotected vaginal intercourse, F – female, M – male, Mix – data available on mixed gender only, FSW – female sex worker, MSM – men who have sex with men, shebeen – an informal establishment serving alcohol, STI – sexually transmitted infection, VCT – voluntary counselling and testing, ACASI – audio computer-assisted self-interview, FTFI – face-to-face interview, SAQ – self-administered questionnaire, CRS – cluster random sample, SRS – simple random sample, RDS – respondent-driven sample, RCT – randomized controlled trial a Studies which reported AI prevalence for unprotected AI only. b Sum lower than expected as two studies report on both higher and general-risk populations. c Recall period referred to here as “general” when participants were asked “Do you practise anal sex”, or similar. d Defined by author as “high risk” but no definition provided; sample consists of 79% FSW [70]. …”
Section: Resultsmentioning
confidence: 99%
“…This yields similar interpretations to a recent causal modelling study conducted in over 50 000 adults in North America and Europe. 39 Preliminary findings from the START and TEMPRANO trials point towards a morbidity benefit of immediate ART initiation but, as Lodi et al 39 have also highlighted, different populations with different co-infections, different follow-up times and different assumptions complicate comparisons between different settings. Furthermore, findings from adults can likely not be transferred to adolescents due to different patient care systems, durations of infection, issues with nonadherence, drug combinations and lifestyle factors.…”
Section: Results In Contextmentioning
confidence: 99%